The Representation, Generalized Binet Formula and Sums of The Generalized Jacobsthal p-Sequence - Daşdemi̇r, Ahmet (Hitit University, 2016)
In this study, a new generalization of the usual Jacobsthal sequence is presented, which is called the generalized Jacobsthal Binet formula, the generating functions and the combinatorial representations of the generalized Jacobsthal p-sequence are investigated. Moreover, certain sum formula consisting of the terms of the generalized Jacobsthal p-sequence are given
Keywords: jacobsthal sequence; binet formula; TA1-2040; Engineering (General). Civil engineering (General); generating matrix; combinatorial representation.; Jacobsthal sequence; Generating Matrix; Binet Formula; Combinatorial representation.